2017
DOI: 10.1111/ecc.12744
|View full text |Cite
|
Sign up to set email alerts
|

Reduced employment and financial hardship among middle‐aged individuals with colorectal cancer

Abstract: Financial hardship may affect up to 30% of cancer survivors, however, little research has addressed the effect of employment change on financial hardship. This study compared the self-reported financial hardship of middle-aged (45-64 years) colorectal cancer survivors (n = 187) at 6 and 12 months following diagnosis with that of a matched general population group (n = 355). Colorectal cancer survivors were recruited through the Queensland Cancer Registry, Australia; data from the Household Income and Labour Dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 24 publications
0
34
1
Order By: Relevance
“…In stratified analyses, CRC-LTS in the <65 year age group reported greater financial difficulties which were of small clinical relevance. This could be due to changes in employment as a study of middle-aged CRC survivors showed that reduced or ceased employment contributes to financial vulnerability within a year after diagnosis [32]. It is intriguing that we find CRC survivors report significant financial problems, albeit of small clinical relevance, as Germany has a universal access health care system.…”
Section: Discussionmentioning
confidence: 80%
“…In stratified analyses, CRC-LTS in the <65 year age group reported greater financial difficulties which were of small clinical relevance. This could be due to changes in employment as a study of middle-aged CRC survivors showed that reduced or ceased employment contributes to financial vulnerability within a year after diagnosis [32]. It is intriguing that we find CRC survivors report significant financial problems, albeit of small clinical relevance, as Germany has a universal access health care system.…”
Section: Discussionmentioning
confidence: 80%
“…The search identified 3945 unique citations (PubMed (n = 2891), Web of Science (n = 775), CINAHL (n = 180), and PsycINFO (n = 99)) with 31 studies meeting our inclusion criteria (Table 2) [8, 18, 20, 21, 26, 29-33, 36-38, 40, 41, 43], 5 studies focused on breast cancer [19,25,28,35,42,44] and 2 included multiple myeloma patients [22,45]. The other studies focused on bladder [39], prostate [23], colorectal [24], lung [27], head and neck cancer [34], and bone marrow transplant patients [17]. Time since diagnosis ranged from a mean of 8.4 months before diagnosis [27] until a mean of 13 years after diagnosis [19] often had a broad range, and sometimes was not reported at all.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Sample sizes ranged from 129 [19] to 16,771 [30] participants. Eight studies had a longitudinal design [19,24,25,27,32,35,42,44]. Both definitions and measures of financial toxicity varied strongly, and most measures were not validated making comparison between studies difficult.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Second, we did not consider the support of employer, coworkers, and the work environment, nor did we consider the job requirements for returning to work . Third, factors such as economic status and social welfare allowances, which may impact the desire to return to work, were not consider in this study . Our study also did not consider personal financial resources or living expenses, which would be an important topic for future studies.…”
Section: Study Limitationsmentioning
confidence: 99%